Protection Coordination with Static Security Assessment - Alam, Mahamad Nabab (2022 IEEE Delhi Section Conference (DELCON), 2022)
Protection coordination considering network security constraints is a challenging task. Power networks are designed to operate properly even under N −1 contingencies caused by the outage of some major components, such as power conductor, transformer, and generator. However, maintaining proper coordination among protective relays is difficult under such contingencies in interconnected power distribution networks. In this paper, the optimum protection coordination scheme of directional overcurrent relays, considering allowable N −1 contingencies, has been presented. This scheme provides a single setting-group of relays to provide proper protection coordination under all allowable contingencies in the system. This protection coordination problem has been formulated as a mixed-integer programming problem and solved using an interior-point method based algorithm. For selecting the allowable contingencies, a composite security index has been used. The effectiveness and suitability of the obtained settings have been demonstrated in the IEEE 14 bus test system.